Hubungan Ibu Hamil Trimester III Dengan Tingkat Kecemasan Dalam Menghadapi Persalinan Di UPTD Puskesmas Trimoharjo - Pratiwi, Widya Sandy; Yuliaswati, Enny; Widiyati, Rina Sri; Handayani, Sri (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Pregnant women will certainly have significant changes and impacts related to physiological and psychological. The occurrence of physiological changes such as nausea, vomiting, an enlarged stomach, and fatigue can certainly affect the mother’s psychology during pregnancy. However, due to physiological and psychological changes that occur during pregnancy, this then triggers feelings of anxiety (anxiety) and feelings of anxiety in the condition of pregnancy. This type of research is analytic using the research design "Cross Sectional" where the independent variable and the dependent variable are examined simultaneously and at one time. Based on the Chi-Square test conducted by the researcher, the X2 value was 36.937> from X2 table 31.410 with a p value of 0.000 < α 0.05, which means that there is a significant relationship between the characteristics of pregnant women in Trimester III with the level of anxiety in facing childbirth in the work area of UPTD Trimoharjo Health Center. There is a significant relationship between the characteristics of third trimester pregnant women and the level of anxiety in facing childbirth in the work area of UPTD Trimoharjo Health Center